2014
DOI: 10.1016/j.febslet.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation control of protein tyrosine phosphatase A activity in Mycobacterium tuberculosis

Abstract: Edited by Zhijie Chang Keywords:Protein tyrosine kinase A Protein tyrosine phosphatase A Protein kinase A Phosphorylation Mycobacterium tuberculosis a b s t r a c t Protein tyrosine phosphatase A (PtpA) has been shown to play a key role in human macrophage infection by Mycobacterium tuberculosis (Mtb). Protein tyrosine kinase A (PtkA) was the first protein tyrosine kinase shown to phosphorylate PtpA. Here, we found that PtkA-mediated phosphorylation of PtPA on Tyr-128 and Tyr-129 enhances the PtPA phosphatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…PtpA also represses host apoptosis by dephosphorylating GSK3a (Glycogen Synthase Kinase 3a) [29] and potentially macrophage's bioenergetics state [30]. Our most recent study showed that PtkA positively regulates PtpA phosphatase activity [31]. Taken together, this set of evidence suggests a potential role for PtkA in the control of PtpA and related pathophysiological events in Mtb.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…PtpA also represses host apoptosis by dephosphorylating GSK3a (Glycogen Synthase Kinase 3a) [29] and potentially macrophage's bioenergetics state [30]. Our most recent study showed that PtkA positively regulates PtpA phosphatase activity [31]. Taken together, this set of evidence suggests a potential role for PtkA in the control of PtpA and related pathophysiological events in Mtb.…”
Section: Introductionmentioning
confidence: 60%
“…In this study, we show that PknD and PknK phosphorylate PtkA and enhance its autophosphorylation activity in vitro. More interestingly, our recent work has shown that PtkA and PknA enhance PtpA phosphatase activity through phosphorylation of tyrosines and threonine residues on PtpA [31]. However, PknA does not effect PtkA phosphorylation, suggesting that phosphorylation might effect other aspects like substrate specificity or affinity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…PtpB subverts the innate immune signaling by blocking ERK1/2 and p38-mediated pathways (70). PtpA has been previously shown to be regulated by PTMs such as S-nitrosylation (92) and phosphorylation (93,94), but no modifications were known to occur on PtpB. This is the first study that depicts the regulation of M. tuberculosis PtpB enzyme activity by any PTM.…”
Section: Lysine Acylation In Mycobacteriamentioning
confidence: 94%